2020
DOI: 10.1093/jrr/rraa013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rectal dose reduction by a hydrogel spacer among 3D conformal radiotherapy, volumetric-modulated arc therapy, helical tomotherapy, CyberKnife and proton therapy

Abstract: This study aimed to evaluate the rectal dose reduction with hydrogel spacer in 3D conformal radiotherapy (3DCRT), volumetric modulated arc therapy (VMAT), helical tomotherapy (HT), CyberKnife (CK) and proton therapy. Twenty patients who had hydrogel spacer for prostate radiotherapy were retrospectively enrolled. Computed tomography (CT) images with or without hydrogel spacer were used to evaluate rectal dose reduction. In total, 200 plans (20 patients × 2 CT images × 5 techniques) were created using the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Saito et al compared the CK plans with and without hydrogel spacer. Interestingly, they reported that the D 2% values of the rectum were 36.10 ± 1.52 and 24.33 ± 1.81 Gy without and with the spacer, respectively, when using more than 150 beams 16 . In our study, the average number of beams was 77 (range, 51–96).…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Saito et al compared the CK plans with and without hydrogel spacer. Interestingly, they reported that the D 2% values of the rectum were 36.10 ± 1.52 and 24.33 ± 1.81 Gy without and with the spacer, respectively, when using more than 150 beams 16 . In our study, the average number of beams was 77 (range, 51–96).…”
Section: Discussionmentioning
confidence: 46%
“…Nowadays, we can use the SBRT technique more safely because of the advent of rectal hydrogel spacers 14‐16 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a hydrogel spacer (SpaceOAR TM System, Augmenix Inc., Waltham, MA) was introduced, and it helped reducing rectal toxicities via the insertion of an absorbable hydrogel between the prostate and rectum 11,12 . The use of a hydrogel spacer stably reduced the rectal dose in all EBRT modalities 13 . Moreover, for high‐precision EBRT, it is important to control inter‐ and intrafractional prostate motion.…”
Section: Introductionmentioning
confidence: 99%
“…stably reduced the rectal dose in all EBRT modalities. 13 Moreover, for high-precision EBRT, it is important to control inter-and intrafractional prostate motion. Among the several radiotherapy modalities, CyberKnife (Accuray, Sunnyvale, CA) can be used to acquire 2D images per 5-150 s by using 2-kV x-ray devices (target locating system [TLS]), resulting in high-precision image-guided radiotherapy.…”
mentioning
confidence: 99%